2022
DOI: 10.3389/fendo.2022.839005
|View full text |Cite
|
Sign up to set email alerts
|

Role of estrogen receptors in health and disease

Abstract: Estrogen receptors (ERs) regulate multiple complex physiological processes in humans. Abnormal ER signaling may result in various disorders, including reproductive system-related disorders (endometriosis, and breast, ovarian, and prostate cancer), bone-related abnormalities, lung cancer, cardiovascular disease, gastrointestinal disease, urogenital tract disease, neurodegenerative disorders, and cutaneous melanoma. ER alpha (ERα), ER beta (ERβ), and novel G-protein-coupled estrogen receptor 1 (GPER1) have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
66
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(68 citation statements)
references
References 295 publications
0
66
1
1
Order By: Relevance
“…ERβ is involved in various diseases and different cancer types of the reproductive tract, as well as in other non-reproductive diseases, such as malignancies of the gastrointestinal tract [ 25 , 26 ]. Although not necessarily transferable to humans, mouse knockout models are a valuable tool to clarify the role of ERβ in health and disease [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ERβ is involved in various diseases and different cancer types of the reproductive tract, as well as in other non-reproductive diseases, such as malignancies of the gastrointestinal tract [ 25 , 26 ]. Although not necessarily transferable to humans, mouse knockout models are a valuable tool to clarify the role of ERβ in health and disease [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Extensive studies have been performed on the role of estrogen receptors in health and disease. ERβ is involved in various malignancies of the reproductive tract, such as endometriosis, breast, ovarian or prostate cancer [ 25 , 26 ]. Studies showed that not only healthy granulosa cells in the ovary express ERβ, but it is expressed also in cells that had transformed from normal proliferating cells to tumor cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In pain modulation, estrogen exerts its biological action by binding to estrogen receptors (ERs) at the gene regulation level ( Chen et al, 2022 ). ERα and ERβ have been detected in the spinal cord ( Chen et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Steroid receptors modulate suites of physiological mechanisms, such as homeostatic functions, growth and development, cellular signaling, sexual differentiation and reproduction, as well as behavior (Szego et al 2003; Whirledge and Cidlowski, 2019). Steroid receptors consist of five major groups: 1) the androgen receptors (ARs), 2) estrogen receptors (ERs), and 3) progesterone receptors (PRs), which mediate the actions of androgens (e.g., testosterone, dihydrotestosterone, and 11-ketotestosterone), estrogens (e.g., estradiol), and progestins (e.g., progesterone) on the development and maintenance of the reproductive, musculoskeletal, cardiovascular, immune, and central nervous systems (reviewed in Brinton et al, 2008; Chen et al, 2022; Davey and Grossmann, 2016; Mani et al 1997), and 4) the glucocorticoid receptors (GRs) and 5) mineralocorticoid receptors (MRs), which facilitate the actions of glucocorticoids (e.g., cortisol) and mineralocorticoids (e.g., aldosterone) on metabolism, growth and development, cardiovascular function, ion transport, and salt balance (reviewed in Pascual-Le Tallec and Lombés, 2005; Timmermans et al, 2019). Prior work suggests that extant steroid receptors evolved from an ancestral estrogen receptor that had estrogen-like functionality and preceded the origin of bilaterally symmetric animals, followed by an ancestral progesterone receptor (Thornton, 2001; Thornton et al, 2003).…”
Section: Introductionmentioning
confidence: 99%